Adiposity and gastrointestinal cancers: epidemiology, mechanisms and future directions. Issue 11 (November 2018) - Murphy, Neil; Jenab, Mazda; Gunter, Marc
Abstract Excess adiposity is a risk factor for several cancers of the gastrointestinal system, specifically oesophageal adenocarcinoma and colorectal, small intestine, pancreatic, liver, gallbladder and stomach cancers. With the increasing prevalence of obesity in nearly all regions of the world, this relationship could represent a growing source of cancers of the digestive system. Experimental and molecular epidemiological studies indicate important roles for alterations in insulin signalling, adipose tissue-derived inflammation and sex hormone pathways in mediating the association between adiposity and gastrointestinal cancer. The intestinal microbiome, gut hormones and non alcoholic fatty liver disease (NAFLD) also have possible roles. However, important gaps remain in our knowledge. For instance, our understanding of how adiposity throughout the life course is related to the risk of gastrointestinal cancer development and of how obesity influences gastrointestinal cancer prognosis and survival is limited. Nonetheless, the increasing use of state-of-the-art analytical methods (such as omics technologies, Mendelian randomization and MRI) in large-scale epidemiological studies offers exciting opportunities to advance our understanding of the complex relationship between adiposity and gastrointestinal cancers. Here, we examine the epidemiology of associations between obesity and gastrointestinal cancer, explore potential mechanisms underlying these relationships and highlight important unanswered research questions. Excess adiposity is a risk factor for many cancers of the gastrointestinal system. In this Review, the authors examine the epidemiological evidence of associations between obesity and gastrointestinal cancer risk and explore the potential mechanisms underlying these relationships. Key points A large body of epidemiological evidence supports a causal relationship between excess adiposity and elevated risk of developing gastrointestinal cancers. With the rising prevalence of obesity worldwide, this relationship could represent a growing source of cancers of the gastrointestinal system. Experimental and molecular epidemiological studies indicate important roles for alterations in insulin signalling, adipose tissue-derived inflammation and sex hormone pathways in mediating the association between adiposity and gastrointestinal cancer. Emerging evidence suggests that the gut microbiome, gut hormones, and non alcoholic fatty liver disease might also have important roles in mediating the obesity-gastrointestinal cancer relationship. The use of state-of-the-art analytical methods (omics technologies, Mendelian randomization, MRI and molecular pathological epidemiology) in large-scale epidemiological studies will probably offer novel insights into the adiposity-gastrointestinal cancer relationship.